Intelligent optimization of node coordination in wireless sensor network - Nik Abd. Malik, Nik Noordini (Institute of Electrical and Electronics Engineers, 2009)
This paper presents a method which intelligently determines the optimum node coordination of sensor nodes topology. The topology is in linear array, aimed for beamforming in Wireless Sensor Networks (WSNs). The array is constructed in random sensor node deployment. The selected nodes should align similar to a uniform linear array (ULA) to minimize the position errors which will improve the beamforming performance (gain, transmission range and characteristics). Instead of utilizing random beamforming which needs a large number of sensor nodes to interact with each other and form a narrow radiation beam, the proposed approach is emphasized to only a number of sensor nodes which can construct a linear array. Beamforming technologies can increase the system performance, increase the transmission range and control the directionality of the reception or transmission of a signal. The proposed work utilizes beamforming technique by using ULA to establish a communication link in a WSN.